An intergenerational approach to parasitoid fitness determined using clutch size - Samková, Alena; Raška, Jan; Hadrava, Jiří; Skuhrovec, Jiří (Scientific reports, 2022)
Parasitoids, as important natural enemies, occur in high numbers and help maintain balance in natural ecosystems. Their fitness is traditionally studied as fertility based on the number of offspring in the F1 generation. Here, using gregarious parasitoids as models, we show that this traditional approach omits one important parameter: the clutch size-body size-fertility correlation among offspring. As a result of this correlation, when females adjust the number of offspring laid in a host, they determine not only the number of offspring produced but also the body size and reproductive potential of those offspring. Although parasitoid fertility has been determined several times from clutch size, here we use Anaphes flavipes to demonstrate the use of this relationship in an upgraded intergenerational approach to parasitoid fitness. We show that with a range of hosts simultaneously utilized by female parasitoids, identical fertility in the F1 generation can lead to distinctly different fertility values in the F2 generation. Even with the same number of hosts, lower fertility in the F1 generation can generate higher fertility in the F2 generation. Our approach provides an intergenerational perspective for determining individual fitness of gregarious parasitoids and new possibilities for the modelling of parasitoid population density.
Keywords: velikost snůšky; Wasps; rozmnožování; Clutch Size; Host-Parasite Interactions; zvířata; ženské pohlaví; interakce hostitele a parazita; Female; Ecosystem; Animals; ekosystém; Reproduction; sršňovití